Evaluation of the Factors of Russian Regions’ Convergence / Divergence in the Level of Budget Provision Based on the Decomposition of the Theil - Bernoulli Index - Marina Yuryevna Malkina (Prostranstvennaâ Èkonomika, 2016)
The study focuses on the Russian regions’ disparities in the level of budget expenditures per capita and their dynamics. The paper assesses contribution of main factors and their correlation, as well as the stages of budget process, to the regional imbalances in the public sector. The author also presents regions’ budget expenditures per capita in a form of five-factor multiplicative model which at the same time demonstrates the sequence of the stages of budget process. To estimate regions’ inequality in budget expenditures and other related variables the researcher employs the Theil - Bernoulli index which is sensitive to excessive poverty. Its decomposition, made on the basis of the Duro and Esteban technique, allows evaluating the structure of inter- regional disparities in the public sector. The results include following: 1) static assessments of the factors contribution to the regions’ convergence in budget expenditure per capita at the stages of GRP production, receipt and distribution of taxes among levels of budget system, the stages of attraction of inter-budgetary support and budget deficit financing; 2) dynamic assessments of the factors contribution to regions’ convergence / divergence in the level of budgetary expenditure per capita for 9 years. The findings may be useful in optimizing the policy of inter-budgetary equalization in Russia